Setting new standards for better MEL. Lessons for grantees & funders - Colnar, Megan; Azevedo, Andrea; Tolmie, Courtney; Caddick, Hannah (Open Society Foundations, 2023)
How can donors and grantees work together to create effective monitori ng, evaluation, and learning (MEL) practices that drive field-wide tra nsformation? The Open Society Foundation’s Fiscal Governance Program f ound success by focusing on six key approaches, including empowering g rantees and relinquishing power. In 2021, an external close-out evalua tion by Intention to Impact of the program (which ran for 7 years and gave over $150 million in grants) revealed something pretty remarkable —the program’s deliberate focus on strengthening field-wide monitoring , evaluation, and learning practices was a success. Substantial capaci ty increases were observed across key institutions and grantees, new c omplexity-sensitive practices and methods were being actively champion ed and deployed, and a growing community of better-connected practitio ners were exchanging tips and tricks on how to apply smart, context-sp ecific MEL across fiscal governance issues. What’s more, in this evalu ation, most grantees gave high praise to these efforts. So, how did th is come about? We detail the six different approaches we used in our n ew publication Setting new standards for better MEL: Lessons for funde rs and grantees. The approaches range from checking power dynamics to growing skills for evaluative thinking and seeding peer learning and f ield-wide research. The publication is paired with a toolkit and showc ases resources we used and iterated on across the various approaches.